Analysis of Antioxidant Activity on the Ethanol Extract of Indonesian Tropical Forest Plants - Anita Rizqiana; Sudarmin Sudarmin (Universitas Negeri Semarang, 2023)
Free radicals can be overcome with the intake of antioxidants in the human body. Antioxidants function to inhibit and neutralize oxidation reactions involving free radicals. Indonesian tropical forest plants consisting of Bajakah tampala, Sarang semut, Akar kuning and Cemara sumatra have potential as antioxidants because of the secondary metabolites contained therein. The four plants were extracted by maceration method and the extracts were then tested for phytochemicals consisting of tests for saponins, tannins, terpenoids, alkaloids and flavonoids. After that, the antioxidant was tested using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and the absorbance was measured using a Uv-Vis spectrophotometer at a wavelength of 517 nm. The results obtained are secondary metabolite compounds contained in Indonesian tropical forest plants including saponins, tannins, and flavonoids. Alkaloid compounds are only owned by the Sarang semut and Akar kuning plants, while terpenoid compounds are owned by the Cemara sumatra and Akar kuning. The antioxidant activity obtained, Sarang semut have the strongest ability with an IC50 value of 4.71 ± 0.30 μg/ml. Cemara Sumatra and Bajakah Tampala are in the very strong category after Sarang semut with IC50 values ​​of 10.54 ± 0.26 μg/ml and 12.86 ± 0.59 μg/ml. While the Akar kuning is included in the medium category with an IC50 value of 137.46 ± 0.80 μg/ml. Comparison of the ability of antioxidant activity from the strongest to the moderate, namely Sarang semut > Cemara sumatra > Bajakah tampala > Akar kuning.